PTIP associated protein 1, PA1, is an independent prognostic factor for lymphnode negative breast cancer. - Takashi Takeshita (Public Library of Science (PLoS), 2013)
Pax transactivation domain interacting protein (PTIP) associated protein 1, PA1, was a newly found protein participating in the modulation of transactivity of nuclear receptor super family members such as estrogen receptor (ER), androgen receptor (AR) and glucocorticoid receptor (GR). Breast cancer is one of the most life threatening diseases for women and has tight association with estrogen and ER. This study was performed to understand the function of PA1 in breast cancer. The expression of PA1 had been evaluated in a total of 344 primary invasive breast cancer samples and examined the relationship with clinical output, relapse free survival (RFS), breast cancer-specific survival (BCSS). PA1 expression was observed in both nucleus and cytoplasm, however, appeared mainly in nuclear. PA1 nuclear expression was correlated with postmenopausal (P = 0.0097), smaller tumor size (P = 0.0025), negative Ki67 (P = 0.02), positive AR (P = 0.049) and positive ERβ (P = 0.0020). Kaplan-Meier analysis demonstrated PA1 nuclear positive cases seemed to have a longer survival than negative ones for RFS (P = 0.023) but not for BCSS (P = 0.23). In the Cox hazards model, PA1 nuclear protein expression proved to be a significant prognostic univariate parameter for RFS (P = 0.03), but not for BCSS (P = 0.20). In addition, for those patients without lymphnode metastasis PA1 was found to be an independent prognostic factor for RFS (P = 0.025), which was verified by univariate and multivariate analyses. These investigations suggested PA1 expression could be a potential prognostic indicator for RFS in breast cancer.